Bevacizumab and irinotecan in recurrent malignant glioma, a single institution experience - Mesti, Tanja (Radiology and oncology (Ljubljana), 2015)
Treatment options of recurrent malignant gliomas are very limited and with a poor survival benefit. The results from phase II trials suggest that the combination of bevacizumab and irinotecan is beneficial. Patients and methods. The medical documentation of 19 adult patients with recurrent malignant gliomas was retrospectively reviewed. All patients received bevacizumab (10 mg/kg) and irinotecan (340 mg/m2 or 125 mg/m2) every two weeks. Patient clinical characteristics, drug toxicities, response rate, progression free survival (PFS) and overall survival (OS) were evaluated. Results. Between August 2008 and November 2011, 19 patients with recurrent malignant gliomas (median age 44.7, male 73.7%, WHO performance status 0%2) were treated with bevacizumab/irinotecan regimen. Thirteen patients had glioblastoma, 5 anaplastic astrocytoma and 1 anaplastic oligoastrocytoma. With exception of one patient, all patients had initially a standard therapy with primary resection followed by postoperative chemoradiotherapy. Radiological response was confirmed after 3 months in 9 patients (1 complete response, 8 partial responses), seven patients had stable disease and three patients have progressed. The median PFS was 6.8 months (95% confidence interval CI: 5.3-8.3) with six-month PFS rate 52.6%. The median OS was 7.7 months (95% CI: 6.6-8.7), while six-month and twelve-month survival rates were 68.4% and 31.6%, respectively. There were 16 cases of hematopoietic toxicity grade (G) 1-2. Non-hematopoietic toxicity was present in 14 cases, all G1-2, except for one patient with proteinuria G3. No grade 4 toxicities, no thromboembolic event and no intracranial hemorrhage were observed. Conclusions. In recurrent malignant gliomas combination of bevacizumab and irinotecan might be an active regimen with acceptable toxicity.
Keywords: bevacizumab; irinotecan; maligni gliomi; rak (medicina); recurrent malignant glioma; sistemska terapija; systemic therapy